2020
DOI: 10.3390/antiox9121302
|View full text |Cite
|
Sign up to set email alerts
|

Use of Parabens (Methyl and Butyl) during the Gestation Period: Mitochondrial Bioenergetics of the Testes and Antioxidant Capacity Alterations in Testes and Other Vital Organs of the F1 Generation

Abstract: Since the mid-1920s, parabens have been widely used as antimicrobial preservatives in processed foods and beverages, pharmaceuticals, and cosmetic products. Paraben use continues to generate considerable controversy, both in the general population and in the scientific community itself. The primary purpose of our study was to determine whether parabens (methyl and butyl at concentrations of 100 and 200 mg/kg body weight by subcutaneous injection) during pregnancy of adult female Wistar rats can have an impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Parabens (PBs) are a group of C-4 esterified molecules of hydroxybenzoic acid (pHBA) with a broad antimicrobial and antifungal spectrum, commonly used since the 1920s [1] as preservatives in foodstuffs, pharmaceuticals, and personal care products (PCPs) to increase their shelf life [2,3]. PBs having a higher value of n-octanol-water partition coefficient (log P ranging from 1.96 to 3.57) show low water solubility, making the shorter-chained PBs better suited for their application.…”
Section: Introductionmentioning
confidence: 99%
“…Parabens (PBs) are a group of C-4 esterified molecules of hydroxybenzoic acid (pHBA) with a broad antimicrobial and antifungal spectrum, commonly used since the 1920s [1] as preservatives in foodstuffs, pharmaceuticals, and personal care products (PCPs) to increase their shelf life [2,3]. PBs having a higher value of n-octanol-water partition coefficient (log P ranging from 1.96 to 3.57) show low water solubility, making the shorter-chained PBs better suited for their application.…”
Section: Introductionmentioning
confidence: 99%
“…In various in vitro and in vivo studies, parabens have been associated with weak estrogenic and anti-androgenic actions ( 331 ). One study demonstrated that paraben use during pregnancy results in significant changes in the mitochondrial bioenergetics and antioxidant capacity of testicular germ cells, as well as the antioxidant capacity of several F1 generation organs, contributing to the understanding of male infertility in future generations ( 332 ). Parabens, especially butyl, can affect the enzymatic antioxidant system in rat testes, leading to a decrease in cellular antioxidant capacity, which may be related to male infertility ( 333 ).…”
Section: Introductionmentioning
confidence: 99%
“…As the antimicrobial additive, it can be found in cosmetics, pharmaceuticals, as well as food products [1][2][3]. In consideration of the estrogenic effects caused by parabens, the application of parabens has aroused the increasing concerns on the latent hazards to health and environment [4,5]. It has been demonstrated that the chronic exposure to BP can cause breast cancer and breast tumors, as well as the impairment of the sperm quality and fecundity [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%